Tinjauan Yuridis Penyaluran Kredit UMKM Di PT. Bank Sumut - Fany, Ajeng Tri; Jamilah, Jamilah; Hidayani, Sri (Jurnal Ilmiah Penegakan Hukum, 2016)
According to Law No. 25 of 2009, what is meant by public services is an activity or a series of activities in the context of fulfilling service needs in accordance with the laws and regulations for every citizen and population of goods, services and / or administrative services provided by public service providers The problem of public service is a problem that cannot be underestimated by this country, because the main task and obligation of the government, both central and regional, is to serve the public. The public service itself can be understood as all forms of service, both in the form of public goods and public services which in principle are the main responsibility and carried out by government agencies in the center and the regions as well as in the State-Owned Enterprises (BUMN) or in the Owned Enterprise Region (BUMD) in order to fulfill the needs of the community and in the framework of implementing the provisions of the legislation.